Social value orientation and regulatory compliance in Ugandan public procurement - Mpeera Ntayi, Joseph; Ngoboka, Pascal; Mutebi, Henry; Sitenda, Gidah (International Journal of Social Economics, 2012)
The purpose of this paper is to examine the perceptions and effects of social value orientation, expected utility, fairness in procurement procedures, the legitimacy of the procurement law and the procurement law enforcement authority on compliance with the procurement law, guidelines, procedures and regulations. Empirical research in this area is relatively sparse. Design/methodology/approach – Data were collected from a sample of 110 Procurement and Disposing Entities (PDEs) and analysed using confirmatory factor analysis (CFA) and structural equation modelling (SEM). Findings – Results of the fit indices between the model and the observed data were generally good for both CFA and SEM. Results reveal that social value orientation, expected utility, legitimacy of the procurement law enforcement agency and perceptions of procedural justice were significant predictors of the Public Procurement and Disposal of Assets Authority (PPDA) regulatory agency. Research limitations/implications – This study however has several limitations which limit the interpretation of results. First, the data are cross sectional, thus limiting monitoring changes in behaviour over time. Second, all item scales adapted in this study were not specifically developed for a public procurement regulatory environment. This means that there is need to develop specific item scales for public procurement regulatory environments. Practical implications – The paper shows that the PPDA regulatory framework should revise its compliance instrument to consider social value orientation. Originality/value – This paper uses constructs of social value orientation, which are largely ignored in legislated professions to predict compliance.
Keywords: Uganda; Public procurement; Social values; Compliance; Social value orientation; Procedural justice; Utility